Farmer Training and coaching has increased the knowledge and implementation of Climate Smart Cocoa Practices among over 1000 cocoa farmers in Ghana - Dalaa, Mustapha Alasan; Saeed, Abdul-Razak; Deffor, Eric Worlanyo; Kofituo, Rich Kofi; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Farmer interviews indicated that all beneficiary farmers have become aware of the CSC recommendations. Field surveys from the Cope and Adjust zones show that the 1113 farmers coached in the climate smart cocoa have implemented practices at various levels. Each farmer has implemented at least 2 climate smart cocoa recommendations in the establishment and management of their cocoa farm. Farmers who implemented CSC practices observed 30-35% increase in the survival rate of transplanted cocoa seedlings. This implies that the implementation of the CSC recommendation has help cocoa seedlings to thrive in both zones in Ghana.